1995
DOI: 10.1002/pro.5560040215
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and rationales for the de novo design of a helical hairpin peptide

Abstract: The de novo design of a t a , a helical hairpin peptide, is described. a t a (u-helix/turn/a-helix) was developed to provide a model system for protein folding at the level of secondary structure association and stabilization. According t o the prevailing models of protein folding, the second step in the folding process is the association and stabilization of secondary structural elements or microdomains. A brief description of the design, along with CD and NMR evidence confirming the conformation of the pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…These substitutions are made in a way that does not affect the formation of helical secondary structure but does encourage the formation of native tertiary contacts between helices, which is the rate-limiting transition state. We designed an amino acid sequence similar to the de novo design of Fezoui et al 36,37 that forms a two-helix bundle in the native state. The two-helix bundle we analyze consists of 41 residues.…”
Section: Sequence Design: Strategic Substitution Of Amino Acids To Rementioning
confidence: 99%
“…These substitutions are made in a way that does not affect the formation of helical secondary structure but does encourage the formation of native tertiary contacts between helices, which is the rate-limiting transition state. We designed an amino acid sequence similar to the de novo design of Fezoui et al 36,37 that forms a two-helix bundle in the native state. The two-helix bundle we analyze consists of 41 residues.…”
Section: Sequence Design: Strategic Substitution Of Amino Acids To Rementioning
confidence: 99%
“…For example, one of the advanced structural models was suggested by Fezoui et al 84,85 for the de novo designed 38-residue helical hairpin peptide. When incubated in aqueous solvent at the neutral pH, this peptide can form the protease resistant fibrils that have the morphologic, structural and tinctorial properties of authentic amyloid fibrils formed by Aβ40 and Aβ42.…”
Section: Wwwlandesbiosciencecom Prionmentioning
confidence: 99%
“…The protein that we investigate is an ␣-helical hairpin peptide which is similar to the de novo designed protein of Fezoui et al 22,23 The designed sequence forms a two-helix bundle in the native state, as shown in Fig. 1.…”
Section: Modelmentioning
confidence: 99%